Prognostic impact of telomere maintenance gene polymorphisms on hepatocellular carcinoma patients with chronic hepatitis B. Issue 5 (27th March 2014) - Jung, Seok Won; Park, Neung Hwa; Shin, Jung Woo; Park, Bo Ryung; Kim, Chang Jae; Lee, Jong‐Eun; Shin, Eun‐Soon; Kim, Jeong A; Chung, Young‐Hwa
<x xml:space="preserve">Abstract</x> Our goal was to determine whether single‐nucleotide polymorphisms (SNPs) of telomere maintenance genes influence the development and clinical outcomes of patients with hepatitis B virus (HBV)‐associated hepatocellular carcinoma (HCC). We evaluated 20 SNPs of five telomere maintenance genes in 702 patients with HCC and 351 hepatitis B virus surface antigen‐positive controls without HCC. Significant SNPs were then validated in an independent cohort of 857 HCC patients and 429 controls. We assessed the association of each SNP with the development of HCC and overall survival through a multivariate Cox proportional analysis. A significantly increased risk of HCC development was identified for the telomerase‐associated protein 1 (TEP1) rs1713449 SNP in both the discovery and replication phases (combined odds ratio = 1.42, P = 9.378 × 10−5). In addition, the TEP1 rs1713449, TEP1 rs872072, protection of telomeres 1 homolog rs7784168, telomerase reverse transcriptase rs13167280, and telomeric repeat binding factor 1 rs2306494 SNPs had a significant effect on the overall survival, and a similar survival effect was validated in the replication cohort. Moreover, there was a significant dose‐dependent association between the number of putatively high‐risk genotypes of the five aforementioned SNPs and overall survival. The median survival time was significantly prolonged for patients with HCC with two or fewer putatively high‐risk genotypes versus those with three or more high‐risk genotypes (85 versus 44 months, log‐rank P = 4.483 × 10−5), and this was demonstrated in the replication cohort (52 versus 37 months, log‐rank P = 0.026). Conclusion: These observations suggest that the SNPs of telomere maintenance genes play a potential role in the development of HCC and the survival of HCC patients with chronic HBV infections. (Hepatology 2014;59:1912–1920)